Between oblivion and exclusive memory. The past of the Jews in the collective memory of the inhabitants of Rzeszow - Malicki, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
This monograph presents the issue of the collective memory of contemporary inhabitants of Rzeszow of the Jews living in the city until 1945. Before the outbreak of the war in 1939 the Jews constituted approximately 1/3 of the 40 thousands of residents of Rzeszow. More than 95% of them were killed in the Holocaust. The survivors left the city soon after the war and today there is not even a small community of that nationality. Almost all the places connected with the Jews (synagogues and cemeteries) were devastated and destroyed. Even though some of them were rebuilt, they have never returned to their functions. After the war, Rzeszow experienced huge socio-spatial changes. This prewar county town was transformed into one of the largest cities in the country, the capital of the province and the regional metropolis with 200 thousands residents in 2022. Postwar socio-demographic processes influenced the creation of a new urban organism where the awareness of the city inhabitants of the unique history is very low. The main objective of the research presented in this work is to diagnose the level of knowledge of the inhabitants of Rzeszow on the history of Jews in the local perspective. Another important goal is practical support for all activities that aim to build the memory of the city's past and its former inhabitants. The history of the Jews is an integral part of the history of Rzeszow. Including this knowledge in the local collective memory can only help foster proactive attitude and involvement in the dynamically developing city.
Keywords: collective memory; sites of memory; commemoration; Jews; Holocaust; Shoah; II world war; Rzeszow; Galicia; Podkarpacie region; pamięć zbiorowa; miejsca pamieci; upamiętnianie; Żydzi; Holokaust; Zagłada; II wojna światowa; Rzeszów; Galicja; region podkarpacki